Geographic distribution of Colombian spittlebugs (Hemiptera: Cercopidae) via ecological niche modeling: a prediction for the main tropical forages’ pest in the Neotropics - Hernández, Luis Miguel; Espitia, Paula A.; Florián, David; Castiblanco, Valheria; Cardoso Arango, Juan Andrés; Gómez-Jiménez, María I. (Frontiers Media, 2021)
Spittlebug complex (Hemiptera: Cercopidae) includes the main tropical pests in Central and South America in cultivated pastures. We aimed to estimate the potential distribution of Aeneolamia varia, A. lepidior, A. reducta, Prosapia simulans, Zulia carbonaria, and Z. pubescens throughout the Neotropics using ecological niche modelling. These six insect species are common in Colombia and cause large economic losses. Records of these species, prior to the 2000 year, were compiled from human observations, specimens from CIAT Arthropod Reference Collection (CIATARC), GBIF, and an extensive literature review. Different ecological niche models (ENM) were generated for each species: maximum entropy (Maxent), generalized linear (glm), multivariate adaptive regression spline (MARS), and random forest model (rf). Bioclimatic datasets were obtained from WorldClim and the 19 available variables were used as predictors. Future changes in the potential geographical distribution were simulated in ENMs generated based on climate change projections for 2050 in two scenarios: optimistic and pessimistic. The results suggest that i) colombian spittlebugs imposes an important threat to Urochloa production in different South American countries, ii) each spittlebug species has a unique geographic distribution pattern, iii) in the future all the six species are likely to invade new geographic areas even in a pessimistic scenario, iv) A. lepidior and A. reducta showed a higher number of suitable habitats across Colombia, Venezuela, Brazil, Peru, and Ecuador, where predicted risk is more severe. Our data will allow to i) monitor the dispersion of these spittlebug species, ii) design strategies for integrated spittlebug management that include resistant cultivars adoption to mitigate potential economic damage, and iii) implement regulatory actions to prevent their introduction and spread in geographic areas where the species are not yet found.